Web-Based Digitalization Of Evaluation Sheets For The Competency Practice Course Of The Air Traffic Management Study Program At The Makassar Aviation Polytechnic - Ida Umboro WNW; Andrian Pratama; Aprinia Kusumaningsih; RD Sanjaya (Letters in Information Technology Education (LITE), 2025)
This article aims to determine the conditions for implementing manual daily evaluation sheets in the ATM Study Program and to develop the digitalization of website-based evaluation sheets. The research method used is the Rapid Application Development (RAD) research method. This method aims to shorten the time needed to plan, design, and implement a system. The respondents selected were 12 people, consisting of 10 lecturers and 2 educational staff members from the ATM study program. The testing technique uses the Black Box Testing method aimed at students, lecturers, and educational staff to test each menu on the website created. Test results show that each menu works as expected. So it can be concluded that the digital evaluation sheet is successful because lecturers can easily input the grades for practicum activities and education staff can easily monitor practicum results and summarize student assessment data.